(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To identify the factors influencing the caregiving burden among family caregivers of cancer patients. Materials and methods: A cross-sectional descriptive study was conducted on 252 caregivers at the Oncology Center — Hanoi Medical University Hospital, from December 2023 to May 2024. Data were collected using a structured questionnaire, including: general characteristics of caregivers and patients, the Zarit Burden Interview (ZBI) to assess caregiving burden, the Caregiver Quality of Life Index-Cancer (CQOL-C) to assess caregivers’ quality of life, and the Barthel Index (BI) to assess patients’ functional dependency. Results: The study revealed significant differences in caregiving burden according to caregiver gender (p < 0.001), occupational groups (p = 0.001), patient gender (p = 0.018), disease classification (p < 0.001), and disease stage (p < 0.001). Caregiver age, patient age, and daily caregiving time were positively correlated with the caregiving burden. The more dependent the patient was, the greater the burden experienced by the caregiver. Additionally, changes in caregivers’ quality of life were significantly associated with the level of caregiving burden. Conclusion: Caregivers who are female, older, have less flexible occupations, and care for male patients or patients of advanced age and later disease stages tend to experience a higher caregiving burden. The burden is generally lower when caring for patients with thyroid cancer compared to other types of cancer. Patient dependency is a key factor that significantly increases the caregiving burden. Moreover, caregivers’ quality of life is positively correlated with the level of caregiving burden.